Effects of silvicultural management on richness, composition and floristic diversity in a tropical rainforest in the lowlands of Costa Rica - Delgado Rodríguez, Luis D. (1995)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 1995